LIABILITY OF MOBILE PHONE SERVICE TECHNICIANS FOR DAMAGE OCCURRING DURING REPAIRS ACCORDING TO THE MALIKI SCHOOL OF LAW - Tiara Balqiest; Amal Hayati (Program Pascasarjana UIN Sumatera Utara, 2026)
The development of mobile phone service as a necessity of modern society has not been fully followed by clear legal accountability for damaged goods and loss of consumer data. Informal service practices, minimal transparency, and the absence of clear boundaries of responsibility often create legal uncertainty and are detrimental to consumers. This study aims to analyze the accountability practices of mobile phone service personnel in Medan Perjuangan District and assess them from the perspective of Maliki Islamic jurisprudence as formulated in the book Al-Muwaṭṭa’. The study uses an empirical juridical approach with qualitative methods through interviews and literature studies. The results show that mobile phone service practices do not fully reflect the principles of trust, clarity of contracts, and responsibility (ḍamān), especially in cases of additional damage and loss of consumer data. From the Maliki perspective, control of consumer goods during the service process gives rise to legal liability obligations, unless the risks have been clearly explained and agreed upon from the beginning of the contract. The novelty of this research lies in the integration of empirical data with Maliki fiqh analysis based on Al-Muwaṭṭa’ to formulate a fairer and more relevant service accountability framework for contemporary muamalah practices.